2015
DOI: 10.1007/s10452-015-9518-3
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the importance of top-down and bottom-up controls in food webs of Chinese lakes through structural equation modeling

Abstract: Zooplankton is generally affected by both top-down and bottom-up regulations in aquatic ecosystems. However, the relative strength of topdown and bottom-up control's on zooplankton assemblages is not well understood. Here, we analyzed this question in five lakes of the Yangtze River basin, an area with high population density and thousands of lakes, many of them suffering multiple environmental pressures. We sampled the whole communities of five lakes in the middle reaches of Yangtze River basin from 2006 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 64 publications
(75 reference statements)
2
19
0
Order By: Relevance
“…Our study showed that the bottom-up effects of physical-chemical variables on phytoplankton were stronger than the top-down effects of zooplankton in both Nansi and Dongping lakes, which is consistent with previous studies [17,18,26]. The growth and reproduction of phytoplankton were influenced by physical-chemical factors in the water [27,28], among which water temperature and nutrient concentration contributed more than the other factors.…”
Section: The Response Of Phytoplankton To Bottom-up and Top-down Effectssupporting
confidence: 91%
“…Our study showed that the bottom-up effects of physical-chemical variables on phytoplankton were stronger than the top-down effects of zooplankton in both Nansi and Dongping lakes, which is consistent with previous studies [17,18,26]. The growth and reproduction of phytoplankton were influenced by physical-chemical factors in the water [27,28], among which water temperature and nutrient concentration contributed more than the other factors.…”
Section: The Response Of Phytoplankton To Bottom-up and Top-down Effectssupporting
confidence: 91%
“…These more complex models often contain numerous multivariable pathways of scientific interest and place a premium on broad, general questions about the relative importance of different ecological flows, such as top‐down vs. bottom‐up control in ecosystems (Du et al. ), the relative importance of environmental vs. biotic drivers in community organization (Laughlin and Abella , Byrnes et al. , Cronin et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also an increasingly recognized need to work with complex models that correspond more closely with system-level questions (Mitchell 2001, Forister et al 2011, Lamb et al 2014, Fan et al 2016. These more complex models often contain numerous multivariable pathways of scientific interest and place a premium on broad, general questions about the relative importance of different ecological flows, such as top-down vs. bottom-up control in ecosystems (Du et al 2015), the relative importance of environmental vs. biotic drivers in community organization (Laughlin and Abella 2007, Byrnes et al 2011, Cronin et al 2014, Gama-Rodrigues et al 2014, Jing et al 2015, or the relative importance of different biotic processes (Cardinale et al 2009, Scherber et al 2010, Mazancourt et al 2013. For applications such as these, standardization methods that provide clear comparability among coefficients and also that can summarize indirect and total effects become of great importance.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…From the basic estimate of the model, the biomass of fish groups in the TSL ecosystem was estimated at 58 t km −2 higher than the estimated biomass of fish groups in Lake Victoria (43 t km −2 ) and Lake Tanganyika (35 t km −2 ) (Christensen and Pauly, 1993). The relatively high biomass of the top predators in TSL could produce a predation pressure on its forage species through the top-down controls in the food web (Du et al, 2015). The catch statistics from the lake showed that snakehead and catfish were found to be abundant in the TSL system since TSL and its floodplains are suitable feeding and spawning grounds for many carnivore species .…”
Section: Food Web Structure In Tslmentioning
confidence: 99%